New ATRP initiator for synthesis of cyclic carbonate-terminated poly(methyl methacrylate) - Palaskar, Dnyaneshwar V.; Sane, Prakash S.; Wadgaonkar, Prakash P. (Reactive & Functional Polymers, 2010)
A new ATRP initiator, viz, 2-oxo-1,3-dioxolan-4-yl-(methyl-2-bromo-2-methylpropanoate) (ODMBMP) was synthesized by the reaction of commercially available glycerol carbonate with 2-bromoisobutyrylbromide and was used to carry out ATRP reactions of methyl methacrylate (MMA) in the presence of copper chloride/N,N',N',N''N''-pentamethyldiethylenetriamine to afford low molecular weight (M(n)(GPC) = 1750-7550) cyclic carbonate-terminated poly(methyl methacrylate)s with relatively narrow molecular weight distribution (M(w)/M(n) = 1.16-1.30). Poly(methyl methacrylate)s having higher molecular weight (M(n)(GPC) = 18,250 and 44,130) could also be synthesized using ODMBMP as the ATRP initiator. The kinetic studies of bulk ATRP of MMA showed a linear relationships between both In[M](o)/[M(t)] vs time and molecular weight vs conversion indicating controlled/living polymerization. The presence of cyclic carbonate functionality in poly(methyl methacrylate)s was confirmed by FUR. (1)H NMR, and (13)C NMR spectroscopy. The reactivity of cyclic carbonate group was demonstrated by a model reaction using n-propyl amine and the results showed quantitative conversion to hydroxyl urethane group. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Atom transfer radical polymerization (ATRP); cyclic carbonate; functional polymers; poly(methyl methacrylate)

Synthesis of bis-allyloxy functionalized polystyrene and poly (methyl methacrylate) macromonomers using a new ATRP initiator - Sane, Prakash S.; Palaskar, Dnyaneshwar V.; Wadgaonkar, Prakash P. (European Polymer Journal, 2011)
A new bis-allyloxy functionalized ATRP initiator, viz, 4,4-bis (4-(allyloxy) phenyl) penty1-2-bromo-2-methylpropanoate was synthesized starting from commercially available 4,4-bis (4-hydroxyphenyl) pentanoic acid. Atom transfer radical polymerization of styrene in bulk and that of methyl methacrylate in anisole using CuBr/N,N,N',N',N `'-pentamethyldiethyl-enetriamine system was carried out. The kinetic study of styrene polymerization showed controlled polymerization behavior. Bis-allyloxy functionalized well-defined polystyrene (M(n)(GPC): 13,600-28,250, PDI: 1.07-1.09) and poly (methyl methacrylate) (M(n)(GPC): 10,100-18,450, PDI: 1.23-1.34) macromonomers were obtained. The presence of allyloxy functionality was confirmed by (1)H NMR spectroscopy. The reactivity of allyloxy functionality was demonstrated by carrying out organic reactions such as addition of bromine and hydrosilylation on polystyrene macromonomer. Polystyrene macromonomer with bis-allyloxy functionality was transformed into bis-epoxy functionalized polystyrene macromonomer using 3-chloroperoxybenzoic acid. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Allyloxy end-functional polymer; Atom transfer radical polymerization (ATRP); Macromonomers; Poly (methyl methacrylate); Polystyrene

Aromatic aldehyde functionalized polycaprolactone and polystyrene macromonomers: synthesis, characterization and aldehyde-aminooxy click reaction - Sane, Prakash S.; Tawade, Bhausaheb V.; Palaskar, Dnyaneshwar V.; Menon, Shamal K.; Wadgaonkar, Prakash P. (Reactive & Functional Polymers, 2012)
New bis-aldehyde functionalized initiators, viz, 4,4'-(4,4'-(5-hydroxypentane-2,2-diyl)bis(4,1-phenylene))bis(oxy)dibenza ldehyde (1) and 4,4'-bis(4-(4-(formylphenoxy) phenyl) pentyl 2-bromopropanoate (2) were synthesized starting from commercially available 4,4'-bis(4-hydroxyphenyl) pentanoic acid. These initiators were utilized, respectively, for ring opening polymerization of E-caprolactone and atom transfer radical polymerization of styrene. Well-defined polycaprolactone macromonomers (M-n(GPC): 2600-19400, PDI: 1.37-1.47) and polystyrene macromonomers (M-n(GPC): 2800-28200, PDI: 1.11-1.16) with bis-aldehyde functionality were synthesized. The kinetic study of styrene polymerization showed controlled polymerization behaviour. The presence of aldehyde functionality in macromonomers was confirmed by H-1 NMR spectroscopy. The reactivity of aldehyde functionality was demonstrated by carrying out aldehyde-aminooxy click reaction of polycaprolactone macromonomer with O-(2-azidoethyl) hydroxylamine which proceeded in a quantitative manner without backbone degradation. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Aldehyde-terminated macromonomers; ATRP; Polycaprolactone; Polystyrene; ROP